Relationship Between Middle Facet Peritalar Subluxation and the Severity of Flatfoot Deformity. Issue 4 (22nd October 2020) - Baumfeld, Daniel; Silva, Thiago A.; Li, Shuyuan; Mansur, Nacime S.; Dibbern, Kevin N.; Cychosz, Chris; Lintz, Francois; Godoy-Santos, Alexandre L.; Goetz, Jessica E.; Femino, John E.; de Cesar Netto, Cesar
Category: Hindfoot; Midfoot/Forefoot; Other Introduction/Purpose: Recent literature has established the middle facet of the subtalar joint as a reliable and accurate marker of pronounced peritalar subluxation (PTS) in Adult Acquired Flatfoot Deformity (AAFD) patients. The Foot and Ankle Offset (FAO) has also been accepted as a more complete and three-dimensional (3D) measurement of foot collapse and hindfoot valgus. To date, no assessment has been made regarding the relationship between the severity of the AAFD and the amount PTS measured at the middle facet. The objective of this study was to investigate the correlation between these variables. We hypothesized that direct positive linear correlation would be found, with significantly increased middle facet joint incongruence and subluxation in patients with more pronounced hindfoot valgus and foot collapse. Methods: In this IRB-approved retrospective comparative study, we included 76 feet (42 left, 35 right) with symptomatic AAFD who underwent standing weightbearing CT (WBCT) as standard baseline assessment of their foot deformity. One blinded fellowship-trained foot and ankle surgeon with more than 10 years of experience performed measurements using multiplanar reconstruction (MPR) WBCT images. Manual measurements of subluxation and incongruence of the middle facet were performed at the anteroposterior midpoint of the articular facet. Semiautomatic calculation of the FAO was performed after 3D coordinate harvesting of the weightbearing points of the first, fifth metatarsal and calcaneus as well as the center of the ankle. Correlation of FAO severity and subluxation/incongruence of the middle facet was assessed by Spearman's correlation and bivariate analysis. Paired Wilcoxon was utilized to compare FAO values in congruent (0% subluxation), subluxated (1-99% subluxation) and dislocated middle facets. P-values <0.05 were considered significant. Results: No significant direct correlation was observed between FAO and Middle Facet Incongruence angle (p=0.12). However, positive linear correlation was found between middle facet subluxation and FAO (Spearman's 0.54, R2 0.29, p<0.0001). The subluxation of the middle facet was found to increase by 3.5% for every one-point FAO increase (Middle Facet Subluxation (%) = 6.903202 + 3.5452074*Foot and Ankle Offset). Mean values and confidence intervals (CI) of FAO were significantly different depending on the congruency of the middle facet (p=0.0003): congruent, 5.2 (CI, 3.4 to 7.0), subluxated, 8.7 (CI, 6.8 to 9.0) and dislocated, 12.9 (CI, 9.8 to 15.9). Similarly, middle facet subluxation was also found to progressively and significantly increase when FAO values were staged from zero (normal alignment) to four (FAO>20) (p<0.0001). Conclusion: This study is the first to compare and correlate measurements regarding the amount of subluxation of middle facet with the severity of AAFD, when measured by the foot and ankle offset (FAO). We found a significant, positive and linear correlation between the amount of subluxation of the middle facet and FAO measurements. No correlation was found between the incongruence angle of the facet and FAO. Our results support the concept of using the subluxation of the middle facet of the subtalar joint as a key marker of early and progressive deformity in patients with AAFD.